SOME DIFFERENCES OF THE POETIC AND POETIC AND PROSAIC VARIANTS OF THE POEM (Scientific journal of the Fergana State University, 2023)
In the given article the differences in the poetic and prose variants of the poem “Saddy Iskandary” on the example of the concept “gift”  are analyzed